Gestión administrativa – económica – financiera y su incidencia en la operatividad de la liga deportiva cantonal de Quevedo, año 2017 - Bersoza Yépez, Félix Arnaldo (2018)
This research focused on administrative, economic and financial management and its impact on the operation of the Cantonal Sports League of Quevedo, 2017. The work addressed the need to provide the sports entity with an instrument to efficiently and effectively conduct activities internal to the administrative process and the proper management of resources for proper operation. The approach of the objectives responded to: Examine the administrative management system, estimate the impact caused by economic management on the activities, analyze the financial management system developed and determine the level of operation of the Cantonal Sports League of Quevedo. Methodologically, the proposal was framed in different methods and techniques that allowed the collection of appropriate information regarding the poor administrative, economic and financial management that influences the timely decision making that leads to institutional success. Among the results it stands out that administratively it is breached with the current regulations in 100%, resort to the application of statutes to regulate the resolutions and decision making in the sports entity. As for the financial evaluation, it reflected 50% that the financial information is unreasonable due to the lack of control over the management of the budget. Operationally, it is proposed to the board of directors to take the corresponding measures to correct the shortcomings in administrative, economic and financial order to improve the perception of internal clients about the institution. Key words: Administrative management - efficiency - results - financial operability